Dampak Prinsip Etika Bisnis Islam Pada Peningkatan Ekonomi Pedagang Kaki Lima di Kota Jambi - Aslamia, Dita; Desviona, Nayla; Oktaria, Cindy; Nur, Azkia Firanti (Pusat Penelitian dan Pengabdian (P3M) STKIP Majenang, 2025)
This research is a quantitative study which aims to analyze how Islamic business ethics influence the economic growth of street vendors in Jambi City. Street Vendors (PKL) often face various problems in running their business. The Islamic economic system exists as a solution to overcome these problems. The application of Islamic business ethics has an important role in running a business in accordance with religious principles. This research uses qualitative methods with a literature study approach to analyze the application of Islamic business ethics in increasing the income of Street Vendors (PKL). The research results show that the application of Islamic business ethics can increase the awareness of business people and have a positive impact on Street Vendors (PKL).